Living in more than one world : how Peter Drucker's wisdom can inspire and transform your life - Rosenstein, Bruce (BK life book., 2009)
Synthesizing management legend Peter Drucker's simple yet profound core teachings into a guide to personal and professional transformation, this work shows readers how to apply Drucker's recommendations to lead more fulfilling and meaningful lives.